2021 Asia‐Pacific League of Associations for Rheumatology clinical practice guideline for treatment of gout. (20th December 2021) - Lorenzo, Jose Paulo P.; Sollano, Ma. Hanna Monica Z.; Salido, Evelyn O.; Li‐Yu, Julie; Tankeh‐Torres, Sandra A.; Wulansari Manuaba, Ida Ayu Ratih; Rahman, Md Mujibur; Paul, Binoy J.; Mok, Mo Yin; De Silva, Monika; Padhan, Prasanta; Lim, Ai Lee; et al.
Abstract: Background: Gout is the most prevalent inflammatory arthritis in the Asia‐Pacific region and worldwide. This clinical practice guideline (CPG) aims to provide recommendations based on systematically obtained evidence and values and preferences tailored to the unique needs of patients with gout and hyperuricemia in Asia, Australasia, and the Middle East. The target users of these guidelines are general practitioners and specialists, including rheumatologists, in these regions. Methods: Relevant clinical questions were formulated by the Steering Committee. Systematic reviews of evidence were done, and certainty of evidence was assessed using Grading of Recommendations Assessment, Development and Evaluation methodology. A multi‐sectoral consensus panel formulated the final recommendations. Results: The Asia‐Pacific League of Associations for Rheumatology Task Force developed this CPG for treatment of gout with 3 overarching principles and 22 recommendation statements that covered the treatment of asymptomatic hyperuricemia (2 statements), treatment of acute gout (4 statements), prophylaxis against gout flare when initiating urate‐lowering therapy (3 statements), urate‐lowering therapy (3 statements), treatment of chronic tophaceous gout (2 statements), treatment of complicated gout and non‐responders (2 statements), treatment of gout with moderate to severe renal impairment (1 statement), and non‐pharmacologic interventions (5 statements). Conclusion: Recommendations for clinically relevant scenarios in the management of gout were formulated to guide physicians in administering individualized care.